Can hyena behaviour provide information on population trends of sympatric carnivores?. (16th September 2019) - Green, David S.; Farr, Matthew T.; Holekamp, Kay E.; Strauss, Eli D.; Zipkin, Elise F.
Abstract : Mammalian carnivores are declining worldwide owing to human activities. Behavioural indicators have the potential to help identify population trends and inform conservation actions, although this area of research is understudied. We investigate whether behaviour is linked to abundance in a community of carnivores in the Masai Mara National Reserve, Kenya. Anthropogenic disturbance increased exponentially in parts of the Reserve between 1988 and 2017, mainly owing to daily incursions by large numbers of livestock and tourists. Previous research showed that hyena behaviour changed markedly during this period. Through a series of vignettes, we inquire whether hyena behaviours correlate with changes in abundance of hyenas themselves, or those of other carnivore species in the region. We find that changes in spotted hyena behaviour in disturbed areas, but not in undisturbed areas, can be linked to changes in their demography (vignette 1). We also find that declines in observed lion–hyena interactions, as well as increases in spotted hyena abundance, are probably caused by competitive release of hyenas from declining lion abundance (vignette 2). Finally, we demonstrate that in some cases, hyena behaviour and demography is linked to the density and distribution of sympatric carnivores, and that behavioural changes in hyenas can provide information on shifts within the carnivore community (vignettes 3 and 4). Our vignettes reveal intriguing relationships between behaviour and demography that should be explored in future research. Pairing behavioural studies with more traditional monitoring efforts can yield useful insights regarding population and community trends, and aid wildlife conservation and management. This article is part of the theme issue 'Linking behaviour to dynamics of populations and communities: application of novel approaches in behavioural ecology to conservation'.